Strategi Pemulihan Pariwisata Pasca Pandemi Covid19 di Kabupaten Sumenep - Ida Syafriyani; Sofiyah Qamariah (Faculty of Social and Political Science, 2023)
Since early 2020, all countries in the world have been hit by the 2019 coronavirus (Covid-19) pandemic, including Indonesia. The COVID-19 pandemic not only affects public health, but also has an impact on the economy. Meanwhile, the tourism sector experienced a slump. The purpose of this study is to find out the Tourism Recovery Strategy after the Covid-19 Pandemic in Sumenep Regency. This study uses a qualitative method. The post-pandemic tourism recovery strategy includes three parts, namely strategy formulation, strategy implementation, and strategy evaluation. The strategy formulation is an elaboration of central government regulations, namely the application of CHSE (Clealinees, Healthy, Safety, and Environmental Sustainability) in the main activities in the tourism industry, namely MICE (Meetings, Incentives, Conventions, and Exhibitions) and the Enforcement of Restrictions on Community Activities. Furthermore, the central regulation is described in a regional regulation, namely the Decree of the Regent of Sumenep concerning the Enforcement of Restrictions on Community Activities. The implementation of the strategy carried out is the dissemination of the application of health protocols to tourism objects and the surrounding area, which has been implemented since 2020 to all tourism stakeholders (Government, tourism business actors, community). Meanwhile, the strategy evaluation was carried out on the implementation of the strategy as a consideration for improving the strategy in the next period according to the pandemy level, and the situation and conditions in Sumenep Regency. This evaluation is stated in the recommendation of the Regent of Sumenep regarding the implementation of health protocols on 3 tourism objects managed by the Government of Sumenep Regency, namely Slopeng beach, Lombang beach and the palace museum.